Breakthroughs, lags, and contradictions: an analysis of the practices and effects of new media art aesthetic education in China - Zhao, Xiaorong (Frontiers in Education, 2025)
The paper takes the evolution of China’s aesthetic education policy as its entry point to elucidate the intrinsic driving forces behind the development of aesthetic education. Political ideology, labor, and moral education are often interwoven, and these aims have simultaneously provided an opportunity for new media art to engage with aesthetic education. Under the policy support of the Ministry of Education’s new round of aesthetic education immersion initiatives, new media art has undertaken a series of reforms, innovations, and experiments—employing interactive and immersive methods—to enhance and expand aesthetic experiences. Due to the alignment of certain concepts with those in traditional philosophy, it has garnered institutional favor. Research indicates that new media art-based aesthetic education possesses notable advantages in cultivating imagination, creativity, and other capacities in the digital age; however, despite its rapid development propelled by policy momentum, it still faces challenges such as a shortage of qualified educators and a narrow understanding of aesthetic education—issues that may paradoxically give rise to a dilemma rooted in deeper systemic contradictions.